Studying the preparation of activated carbon from macadamia nut shells by chemical activation with NAOH in Methylene Blue treatment application - Doan , Nguyen Hoang Anh; Pham , Mai Ly; Dao , Minh Trung (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
Study on preparation of activated carbons by chemical activation with NaOH using the impregnatio ratio of 3:1 (NaOH:char) from Macadamia nut shell in terms on temperature and time. The research result showed that Methylene Blue (MB) absorption at optimum temperature and time of 300oC and 90 minutes was 205,68 mg and the removal efficiency was 97,59% corresponding to the color reduction from 349,67 Pt-Co to 8,4 Pt-Co. This results showed that activated carbons prepared from Maccadia nut shells and chemical activation with NaOH had the capable of color treatment in textile wastewater.